Scrambler therapy in the management of somatosensory signs and symptoms related to neuropathic pain: an exploratory and prospective analysis - Russo, Domenico; Zoratto, Federica; Tirocchi, Gastone; Guarda, Michela (Acta Biomedica Atenei Parmensis, 2018)
Objectives: Neuropathic pain is a severe and disabling health problem, often difficult to treat and characterized by specific somatosensory signs and symptoms. The goal of this study is to detect the effect of Scrambler therapy (ST) on the reset of Neuropathic Pain Diagnostic Questionnaire (DN4), in a cohort of patients affected by intense drug-resistant neuropathic pain. Methods: Patients with chronic neuropathic pain were consecutively enrolled to receive 45-minute daily ST for an average of 10 consecutive days. Evaluation of pain intensity by Numerical Rating Scale (NRS) score and DN4 questionnaire was performed at the beginning and at the end of the treatment. Primary endpoint was to achieve a significant negativization of DN4 (DN4